Exercise-Induced Bronchoconstriction Identified Using the Forced Oscillation Technique - Seccombe, Leigh M.; Peters, Matthew J.; Buddle, Lachlan; Farah, Claude S. (Frontiers in Physiology, 2019)
Objective: Lung mechanics using the forced oscillation technique (FOT) is suggested to be equivalent and more sensitive in determining exercise induced bronchoconstriction (EIB) than spirometry. Dynamic alterations in minute ventilation (VE) may affect this measurement. We investigated changes in FOT parameters post exercise challenge (EC) in people with asthma as compared to spirometry. The rate of recovery and any effect of raised VE following exercise on FOT parameters was also assessed. Method: Airway resistance (R5) and reactance (X5) at 5Hz and VE were measured prior to forced expiratory volume in one second (FEV1) before and up to 20min after a standard EC in people with asthma and healthy controls. Airway hyperresponsiveness to the hyperosmolar mannitol test was measured in the asthmatic subjects within one week of the EC. Baseline and sequential measures were assessed using repeated measures ANOVA and Pearson’s correlation. Group demographics and recovery data were compared using an unpaired t-test. Results: Subjects with current asthma (n=19, mean±SD age 28±6 yr) and controls (n=10, 31±5 yr) were studied. Baseline FEV1, R5, X5 and VE were similar between groups (p>0.09). Airway hyperresponsiveness was present in 12/19 asthmatic subjects. The EC max %change of R5 and X5 correlated with FEV1 (r>0.90) and were only different to controls in those with asthma that responded by FEV1 criteria (p<0.01). EC recovery of R5 was similar to FEV1, however X5 was greater (p=0.03). Elevated VE post EC did not affect the %change in FOT parameters across all subjects (p>0.3). R5 and X5 were highly sensitive in determining a positive EC response (80-86%) but X5 was more specific (93 Vs 80%). Conclusion: FOT parameters tracked with forced maneuvers and were not influenced by increased ventilation following an exercise challenge designed to elicit EIB. FOT identified EIB similarly to spirometry in patients with asthma.